Sacral nerve stimulation lead implantation in partial sacral agenesis using intra‐operative computerized tomography. (September 2016) - Castillo, J.; Cristóbal, L.; Alonso, J.; Martín, R.; Suárez, D.; Martínez, M. A.; Cagigas, C.; Gómez‐Ruiz, M.; Gómez‐Fleitas, M.; Vázquez‐Barquero, A.
Abstract: Aim: Sacral nerve stimulation (SNS) lead implantation is a straightforward procedure for individuals with intact spinal vertebrae. When sacral anomalies are present, however, the anatomical and radiological reference points used for the accurate placement of the electrode may be absent or difficult to identify. Method: We describe an innovative surgical procedure of percutaneous nerve evaluation for SNS in a patient with faecal incontinence secondary to a congenital imperforate anus and partial sacral agenesis using a surgical imaging platform (O‐arm system) under neurophysiological control. Results: Using intra‐operative CT and neuronavigation, the insertion point at the skin was identified. The lead was introduced into the right‐sided S3 foramen and placed at the correct depth. An appropriate motor response was obtained after stimulation and neurophysiological control confirmed that the right S3 root was being stimulated. Conclusion: Our experience showed that O‐arm guided navigation can be used to overcome the difficulty of SNS lead placement in patients with partial sacral agenesis who have faecal incontinence.